Effect of Oxygen and Redox Potential on Glucose Fermentation in Thermotoga maritima under Controlled Physicochemical Conditions. (24th February 2011) - Lakhal, Raja; Auria, Richard; Davidson, Sylvain; Ollivier, Bernard; Dolla, Alain; Hamdi, Moktar; Combet-Blanc, Yannick
Abstract : Batch cultures of Thermotoga maritima were performed in a bioreactor equipped with instruments adapted for experiments performed at 80 ∘ C to mimic the fluctuating oxidative conditions in the hot ecosystems it inhabits. When grown anaerobically on glucose, T. maritima was shown to significantly decrease the redox potential (Eh) of the culture medium down to about −480 mV, as long as glucose was available. Addition of oxygen into T. maritima cultures during the stationary growth phase led to a drastic reduction in glucose consumption rate. However, although oxygen was toxic, our experiment unambiguously proved that T. maritima was able to consume it during a 12-hour exposure period. Furthermore, a shift in glucose metabolism towards lactate production was observed under oxidative conditions.